2018
DOI: 10.1186/s10194-018-0922-7
|View full text |Cite
|
Sign up to set email alerts
|

Male and female sex hormones in primary headaches

Abstract: BackgroundThe three primary headaches, tension-type headache, migraine and cluster headache, occur in both genders, but all seem to have a sex-specific prevalence. These gender differences suggest that both male and female sex hormones could have an influence on the course of primary headaches. This review aims to summarise the most relevant and recent literature on this topic.MethodsTwo independent reviewers searched PUBMED in a systematic manner. Search strings were composed using the terms LH, FSH, progeste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
108
2
9

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 131 publications
(121 citation statements)
references
References 156 publications
(205 reference statements)
2
108
2
9
Order By: Relevance
“…Some epidemiological studies have shown that several risk factors, including sex [7], body mass index (BMI) [8], smoking [9], family history [10], and climate [11] might be associated with primary headache disorders. Despite the lower prevalence in China, the risk factors are similar to those reported for other countries [12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…Some epidemiological studies have shown that several risk factors, including sex [7], body mass index (BMI) [8], smoking [9], family history [10], and climate [11] might be associated with primary headache disorders. Despite the lower prevalence in China, the risk factors are similar to those reported for other countries [12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…In these cases, migraine seems associated with higher levels of mood disorders, disabilities and menopausal symptoms ( 16 ). The mechanisms of persisting migraine after menopause and hormonal changes in this condition have also been poorly studied ( 17 ).…”
Section: Introductionmentioning
confidence: 99%
“…Men with migraine have also been reported to have higher plasma levels of estrogen than men without migraine (Van Oosterhout et al, 2018). Other hormones, such as testosterone, progesterone, and prolactin, as well as genetic and epigenetic factors, may contribute to these sex-related differences in migraine (Gazerani and Vinterhøj, 2016;Delaruelle et al, 2018;Gazerani, 2019).…”
mentioning
confidence: 99%